Pathological effect of Daily Consumption of Indomy on Lung, Kidney and Spleen in Albino Rat: Sura Fouad AL-Saffar1, Nusaibah Amer2 and Amjed Torki Al-rudaini - AL-Saffar, Sura Fouad (The Iraqi Journal of Veterinary Medicine, 2012)
This study aimed to investigate the histopathological changes of Indomy pasta for 30 days on lung, kidney and spleen of albino rats. fifteen adult albino rats 200-220 gm was divided into 3 groups: The first group was considered as control group. The second group was fed with Indomy every other day for 30 days; the third group was fed with Indomy every day for 30 days. The histopathogical examination of the kidney show congestion of blood vessels and infiltration with neutrophil in lumen, The histopathological examination of lung showed hyper atrophy of masculares layer of the bronchiole with sever inflammatory cell infiltration mainly neutrophil and mononuclear cell in the wall of bronchioles, and with lumen of the alveoli with fibrous connective tissue proliferation in the parenchyma. Also, increase thickness into intra alveolar septa due to paranchymal cell proliferation and mononuclear cell infiltration which lead to narrow alveolar lumen. The histopathogical examination of spleen shows congestion of the red pulp. From the results of this study it can be conclude that the consumption of Indomy had harmful histopathological effects on kidney, lung and spleen tissues in treated rats.